The Accuracy of Lung Ultrasound in Pneumonia Diagnosis: Evidence-Based Case Report - Adityo Wibowo; Airin Aldiani; Faiza Hatim; Galoeh Adyasiwi; Hendra Wahyuni MS; Khairunnisa Imaduddin; Malsephira Hasmeryasih; Mega Juliana; Nesia Priandari; Nina Ratu Nur Kharima; Rudy Satriawan; Agus Dwi Susanto (Jurnal Respirologi Indonesia, 2021)
Background: There are various microorganisms which caused pneumonia in developing countries such as Indonesia. The diagnosjs of pneumonia is still mainly confirmed by Chest X-ray which is unspecific to determine the etiology of pneumonia due to its low accuracy. On the other hand, the higher accuracy diagnostic tool, Computed Tomography (CT) scan, is not cost-effective. Therefore, an alternative diagnostic tool with high precision, affordability, and user-friendly is highly needed. Lung ultrasound (LUS) is an alternative diagnostic device. This study aims to investigate the diagnostic accuracy level of LUS in diagnosing pneumonia. Methods: Literature-researches was done in five databases namely PubMed/MEDLINE, ScienceDirect, Proquest, Cochrane and EBSCO/MEDLINE using keywords according to the clinical scenario. The articles were appraised with CEEBM worksheet. Results: Four articles met the inclusion and exclusion criteria. Sensitivity of LUS ranged around 85-97% and specificity ranged around 8694%. All appraised articles recommended the use of LUS for its high sensitivity in confirming diagnosjs of pneumonia and other lung diseases, and its favorable bedside use especially for critically ill patients. Lung US was also considered as being more inexpensive with less radiation exposure compared to CT scan or other radiographic imaging. Conclusion: Examination using LUS had a high diagnostic value in confirming the diagnosis of pneumonia.